2013
DOI: 10.1590/1414-431x20122409
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chagasic-like arrhythmias in the isolated beating hearts of healthy rats perfused with Trypanosoma cruzi-conditioned medium

Abstract: Chagas' myocardiopathy, caused by the intracellular protozoan Trypanosoma cruzi, is characterized by microvascular alterations, heart failure and arrhythmias. Ischemia and arrythmogenesis have been attributed to proteins shed by the parasite, although this has not been fully demonstrated. The aim of the present investigation was to study the effect of substances shed by T. cruzi on ischemia/reperfusion-induced arrhythmias. We performed a triple ischemia-reperfusion (I/R) protocol whereby the isolated beating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We have previously [ 15 ] demonstrated that cardiac damage can be estimated based on the amount of AST released into the coronary effluent. In the present study, we carried out serial AST enzymatic measurements as an internal control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously [ 15 ] demonstrated that cardiac damage can be estimated based on the amount of AST released into the coronary effluent. In the present study, we carried out serial AST enzymatic measurements as an internal control.…”
Section: Discussionmentioning
confidence: 99%
“…cruzi GP82, [ 13 ] GP90 and GP35/50 proteins [ 31 ] have been described as involved in both the modulation of calcium increase in the host cell and in determining the invasiveness of the parasite strain. Our group [ 15 ], demonstrated that T . cruzi -conditioned medium was able to increase the frequency of occurrence of tachyarrhythmia and cause a decrease in the heart rate during post-ischemic recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cardiac manifestation is considered an arrhythmogenic cardiomyopathy and is characterized by atrial and ventricular arrhythmias and a wide variety of conductive system abnormalities [10]. On the other hand, the presence of fibrosis and hypertrophy was observed in a 3D culture model of T. cruzi infected cardiomyocytes [32,33] and, also, an increase in the frequency of tachyarrhythmias was recorded using infected VERO medium [34], suggesting that T. cruzi secreted proteins have the ability to potentiate arrhythmias, presumably by increasing Ca 2+ intracellular levels. In turn, Epac-mediated activation is necessary for the stimulation of Ca 2+ induced by Ca 2+ release through ryanodine receptors (RyR) in cardiomyocytes [35], while Epac1 depletion protects against myocardial ischemia-reperfusion (I-R) damage, reducing infarct size and cell apoptosis [36].…”
Section: Introductionmentioning
confidence: 99%